Literaturwissenschaft und Bibliotheken - Alker-Windbichler, Stefan; Hölter, Achim (Bibliothek im Kontext, 2015)
Literary studies and libraries have a special relationship with one another. The work of literary scholarship is mainly done in the library, and literary studies have always determined in turn our ideas about libraries. What is this relationship like today? This collection of articles looks for answers in such areas as literary and library theory, the study of libraries as the mediators and suppliers of literature, and scholarship on library subjects and the metaphors relating to libraries
Literaturangaben
Keywords: Aufsatzsammlung; Bibliothek; Information und Dokumentation; Literaturwissenschaft